The Use of Forensic Physician Expertise In View of Health Law Against Murder Cases - Sitompul, Ariman (SASI, 2023)
Introduction: The position of forensic expert evidence stands on the nature of the dualism of expert evidence, on one side of the expert evidence in the form of reports or post mortem et Repertum can still be assessed as expert evidence on the other side of the expert evidence in the form of reports also touches the letter evidence, but decision-making will be the nature of the dualism of forensic expert evidence lies in the confidence of the judge in making a decision. Forensic medicine plays a role in determining the causal relationship between an act and the consequences that will cause injury to the body or cause health problems or cause the death of a person (causal verbend).Purposes of the Research: The purpose of this study is to explain paradiqma conviction and judgment Judge tehadapa Forensic Medicine against murder case.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: The testimony of forensic experts is essentially not binding on the judge. However, in a criminal procedure if it is necessary and the purpose is presented experts to explain the case, explain the cause and effect of the defendant's guilt in committing a criminal act, forensic expert testimony is needed in the trial.